Schoolgirls in Indonesia: Ethnicity, Religion, and Education - Ikasari, Wipsar Siwi Dona (English Education Department, Universitas Islam Indonesia, 2009)
This paper examines major historical and political events during New Order Era (Suharto's regime) and the Reformation Era. These two eras have shaped and continue to shape ethnic and religious identities of Indonesian in contemporary Indonesia. Using four conceptual frameworks of gender, ethnicity, religion and schooling, individual and collective experiences of Indonesian schoolgirls are scrutinized. Indonesian schoolgirls negotiate ethnic and religious practices and traditions as well as global flows of culture, creating new identities. Local cultures are capable of negotiating with the global flows which creates hybridity (Nilan & Feixa, 2006). Nilan's (2006) study in Indonesia shows that Muslim youth in Indonesia can negotiate their Muslimness with the global flows. With several high schools in Indonesia currently pioneering a program of being one of an 'international standard senior high school' to improve education quality and competitiveness in senior high school level, both nationally and internationally, schoolgirls in Indonesia continue to negotiate their identities producing 'hybrid' identities.